Phytochemical Components Analysis by Using Gas Chromatography-mass and Fourier transform- Infrared Techniques of Cressa cretica L. Flowers Extracts (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
This study aimed to investigate the phytochemical components of Cressa cretica L.(flowers) using Gas chromatography- Mass spectrum (GC-MS) and Fourier transform infrared spectrophotometer (FTIR) techniques. The secondary metabolites analysis of C.cretica extracts revealed the presence of phenols, alkaloids, terpenes, flavonoids and glycosides. The results of GC-MS reported thirty chemical compounds  in flower’s extract. The results of the FTIR confirmed the presence of large numbers of  functional groups in flowers of the plant and these functional groups which varied according to the solvent type. More of these functional groups were alcohols, phenols, alkanes, alkyl halides, aldehydes, carboxylic acids, aromatics, nitro compounds and amines.